A Swedish IT forensics course – expert opinions. (29th July 2009) - Davidson, Alan; Oja, Rein; Yngstrom, Louise
There is mounting pressure for institutes of higher education to fill society's need for qualified IT forensics practitioners. Despite that pressure, it is not clear how that need should be filled, for whom, and by whom. There are many published texts available on which one might base a course, though they are primarily written for English speaking countries. Given the differences in legal practices in different countries, and forensic's dependency on legal procedures, it is not clear how applicable such texts are to Swedish education in the subject. This paper summarises some of the ongoing work at the Department of Computer and Systems Sciences at Stockholm University where we seek to define what the primary elements of a Swedish IT forensics education should be. Interviews conducted with specialists in IT law and IT forensics indicate that there are discrepancies between how representatives from on the one hand the public legal system and on the other private enterprise view the need and the subject matter.